Effective Reduction of Acute Ethanol Withdrawal by the Tetracycline Derivative, Tigecycline, in Female and Male DBA/2J Mice. (14th November 2016) - Martinez, Joseph M.; Groot, Jessica A.; Curtis, David C.; Allison, Clayton L.; Marquardt, Patrick C.; Holmes, Ashley N.; Edwards, David S.; Trotter, David R. M.; Syapin, Peter J.; Finn, Deborah A.; Bergeson, Susan E.
Abstract : Background: Alcohol use disorder (AUD) is a spectrum disorder characterized by mild to severe symptoms, including potential withdrawal signs upon cessation of consumption. Approximately five hundred thousand patients with AUD undergo clinically relevant episodes of withdrawal annually ( New Engl J Med, 2003, 348, 1786). Recent evidence indicates potential for drugs that alter neuroimmune pathways as new AUD therapies. We have previously shown the immunomodulatory drugs, minocycline and tigecycline, were effective in reducing ethanol (EtOH) consumption in both the 2‐bottle choice and drinking‐in‐the‐dark paradigms. Here, we test the hypothesis that tigecycline, a tetracycline derivative, will reduce the severity of EtOH withdrawal symptoms in a common acute model of alcohol withdrawal (AWD) using a single anesthetic dose of EtOH in seizure sensitive DBA/2J (DBA) mice. Methods: Naïve adult female and male DBA mice were given separate injections of 4 g/kg i.p. EtOH with vehicle or tigecycline (0, 20, 40, or 80 mg/kg i.p.). The 80 mg/kg dose was tested at 3 time points (0, 4, and 7 hours) post EtOH treatment. Handling‐induced convulsions (HICs) were measured before and then over 12 hours following EtOH injection. HIC scores and areas under the curve were tabulated. In separate mice, blood EtOH concentrations (BECs) were measured at 2, 4, and 7 hours postinjection of 4 g/kg i.p. EtOH in mice treated with 0 and 80 mg/kg i.p. tigecycline. Results: AWD symptom onset, peak magnitude, and overall HIC severity were reduced by tigecycline drug treatment compared to controls. Tigecycline treatment was effective regardless of timing throughout AWD, with earlier treatment showing greater efficacy. Tigecycline showed a dose‐responsive reduction in acute AWD convulsions, with no sex differences in efficacy. Importantly, tigecycline did not affect BECs over a time course of elimination. Conclusions: Tigecycline effectively reduced AWD symptoms in DBA mice at all times and dosages tested, making it a promising lead compound for development of a novel pharmacotherapy for AWD. Further studies are needed to determine the mechanism of tigecycline action. Abstract : Tigecycline, a tetracycline analog, significantly reduced acute ethanol withdrawal symptoms in both female and male C57BL/6J mice in a dose‐responsive manner.